Statistical abstract of the United States. - United States. Bureau of the Census. Data User Services Division; United States. Bureau of the Census. Administrative and Customer Services Division; U.S. Census Bureau (Washington, DC : U.S. Dept. of Commerce, Economics and Statistics Administration, Bureau of the Census, Data User Services Division, 1993)
A statistical reference and guide to over 250 statistical publications and sources from government and private organizations.
Title from title screen.
Publisher varies: U.S. Dept. of Commerce, Bureau of the Census, Administrative and Customer Services Division, 1995-
Issue for 1994- also called 114th- ed.; issue for 2004/2005 is a combined issue.
Adobe Acrobat format or numeric (.wk1 and .xls) files.
Also issued in print.
Some issues also available via the Internet at the Census Bureau web site. Address as of 1/6/98: http://www.census.gov/stat%5Fabstract/; current access is available via PURL.
Keywords: United States -- Statistics -- Periodicals; United States; CD-ROMs.; Periodicals; Statistics; Statistics; Periodicals